2019
DOI: 10.1021/acs.jpcc.8b11919
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Adsorption in Cu3btc2-Type MOFs—Physisorption and Chemisorption as NONOates

Abstract: The adsorption of the biologically important signaling molecule nitric oxide (NO) on two metal−organic frameworks (MOFs), Cu 3 btc 2 and Cu 3 (NHEtbtc) 2 , has been studied by multinuclear solid-state NMR. N-Diazenium diolate (NONOate) formation as primary mode of NO adsorption in the latter MOF is concluded from 15 N, 1 H, and 13 C NMR spectra together with analysis of the 1 H spin−lattice relaxation time (T 1 ). Furthermore, NO adsorption at the open metal site of Cu 3 btc 2 as well as Cu 3 (NHEtbtc) 2 is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 61 publications
0
18
1
Order By: Relevance
“…Polynuclear copper complexes can serve as functional and structural models of multicopper enzymes 16,102,103 . Dinuclear copper complexes constitute important building blocks for materials such as metal-organic frameworks [104][105][106] , and an important test case for electronic structure methods 16,[27][28][29]107 .…”
Section: Gaussian Process Regression (Gpr)mentioning
confidence: 99%
“…Polynuclear copper complexes can serve as functional and structural models of multicopper enzymes 16,102,103 . Dinuclear copper complexes constitute important building blocks for materials such as metal-organic frameworks [104][105][106] , and an important test case for electronic structure methods 16,[27][28][29]107 .…”
Section: Gaussian Process Regression (Gpr)mentioning
confidence: 99%
“…16) was used to load NO which showed NONOate formation additional to the coordination of NO to unsaturated copper centers. 17 However, one of the major shortcomings of MOFs is their instability in the presence of moisture, and some researchers tried to enhance its stability in water or PBS. For example, a modied CuBTC with plasma enhanced chemical vapor deposition of peruorohexane was reported by Decoste et al to prevent the formation of water clusters around the Cu sites.…”
Section: Introductionmentioning
confidence: 99%
“… 16 ) was used to load NO which showed NONOate formation additional to the coordination of NO to unsaturated copper centers. 17 …”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37] Alternatively NO can also be attached to and released from functional moieties incorporated into the organic ligands of MOFs. 38,39 With regards to employing CUSs as the binding mechanism, we have shown that the CPO-27 family of MOFs is particularly effective in this regard. NO binds to the CUSs via a metal-nitrogen coordinate bond and is released from the MOF following substitution by water ( Fig.…”
Section: Introductionmentioning
confidence: 99%